Quality seaport : model building and empirical validation - Mohd Faeiz Ramley. (2010)
The purpose of this paper is to come up with a model for a quality seaport. Although there have been many research on quality in a seaport, there has been limited research done on a model for a quality sea port. The study used a triangulation approach. A rough model is derived from the literature review, which is verified and narrowed down by in-depth interviews, and a survey for empirical validation. The literature review will cover both maritime and non-maritime topics on factors and principles of Quality in general, as well as the principles of the quality gurus. The result of the literature review was a rough model based on 66 factors for a quality seaport. These factors were then regrouped into 14 major factors, as iterated by the interviewees. These factors were surveyed and achieved a 99% confidence interval on the result. Further in-depth interviews were then held to bolster the study. As this is the first stage of a more comprehensive study, the model was tested only with customers. Hence, the empirical data is limited only for the customer-highlighted qualities. Furthermore, research data is limited geographically in Singapore, and may be perceived differently elsewhere. Further research is needed to confirm the primary investigations found in this report, in terms of sample size and the depth of the factors involved.